2001
DOI: 10.4049/jimmunol.166.9.5704
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal T Cells in an Adult Lung Environment Are Competent to Resolve Pneumocystis carinii Pneumonia

Abstract: Initiation of the pulmonary inflammatory response to Pneumocystis carinii is delayed by 3 wk in mice infected as neonates compared with adults. There was no difference in the proliferative response of draining lymph node T cells from mice infected as neonates compared with adults when stimulated in vitro with either Con A or anti-CD3 mAb. However, TNF-α and IFN-γ mRNA expression in the lungs of P. carinii-infected neonates was significantly lower than in adults indicating a lack of appropriate activation signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 44 publications
3
61
0
1
Order By: Relevance
“…It was previously reported that the delayed clearance of Pneumocystis infection seen in mice infected as neonates corresponds to delayed upregulation of proinflammatory cytokines and chemokines (9,33). Surprisingly, there was no difference in the concentrations of TNF-␣, IFN␥, MCP-1, and IL-6 in the BALF of Pneumocystis-infected pups from immunized dams compared to those of pups born to naïve dams through day 19 postinfection (Fig.…”
Section: Vol 72 2004 Antibody-mediated Control Of Pneumocystis In Nmentioning
confidence: 62%
See 3 more Smart Citations
“…It was previously reported that the delayed clearance of Pneumocystis infection seen in mice infected as neonates corresponds to delayed upregulation of proinflammatory cytokines and chemokines (9,33). Surprisingly, there was no difference in the concentrations of TNF-␣, IFN␥, MCP-1, and IL-6 in the BALF of Pneumocystis-infected pups from immunized dams compared to those of pups born to naïve dams through day 19 postinfection (Fig.…”
Section: Vol 72 2004 Antibody-mediated Control Of Pneumocystis In Nmentioning
confidence: 62%
“…It has previously been published that there is a 3-week delay in the host response of mice infected with Pneumocystis as neonates compared to the response of mice infected as adults (8,9,33). To determine whether alveolar macrophage activation is also delayed in neonatal mice in response to Pneumocystis, we used flow cytometry to examine macrophage markers at various times postinfection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have extensive data demonstrating that there is a significant delay in the ability of neonatal mice to clear P. carinii compared to adult mice, and this delay corresponds to delayed activation of alveolar macrophages, delayed entry of CD4 ϩ cells into the lungs, and delayed specific antibody responses to P. carinii (10,15,40). Consistent with our observations in adults, neonatally infected SRAKO mice had elevated numbers of CD4 ϩ cells in the lungs and draining lymph nodes compared to wild-type pups.…”
Section: Discussionmentioning
confidence: 99%